Impact of metal salts on the survival, development, and oviposition behavior of coconut rhinoceros beetle (Coleoptera: Scarabaeidae) - Vowell, Tomie; Manley, Megan E.; Ho, Jordie R.; Watanabe, Shizu; Melzer, Michael J. (Frontiers in Insect Science, 2023)
Oryctes rhinoceros (Coleoptera: Scarabaeidae) is an invasive pest of palms in the Pacific Region, including Hawaii, for which limited management options are available. O. rhinoceros larvae develop in materials rich in organic materials such as green waste and animal manure. Biosolid waste within Hawaii’s infestation zone, however, was determined to inhospitable to O. rhinoceros. To determine if the elevated metal salts present in the biosolid waste was responsible for this observation, O. rhinoceros life stages were acutely and chronically exposed to several metal salts at increasing concentrations to determine the impact of these salts on survival, development, and oviposition behavior. Acute (7 days) exposure to mulch rehydrated in solutions of CaCl2, KCl, MgCl2, or NaCl increasing in concentration from 0 to 0.7 M resulted in increased mortality, with concentrations > 0.5 M generally being 100% lethal to both first and second-instar larvae. A similar trend in survival was observed in subsequent experiments using a horticultural grade of Epsom salt (MgSO4) at 1×, 2×, and 5× the recommended application rate. Chronic exposure (eggs reared on mulch through pupation) to Epsom salt at these same rates resulted in significantly delayed instar development and reduced adult biometrics at both 1× and 2× levels. Similar to the acute exposure, eggs exposed to 5× levels did not hatch, or the first instar died soon after emergence. In choice experiments, gravid females showed no oviposition preference for media hydrated with water or 2× Epsom salt but did avoid ovipositing in mulch rehydrated in 5× Epsom salt. These trials demonstrate a potentially novel approach to managing pest populations of O. rhinoceros.